Sepaktakraw Smash Training Model Based on Training Aids Tool - Wiwik Yunitaningrum; Achmad Sofyan Hanif; Yusmawati Yusmawati; Firmansyah Dlis (PendIPA Journal of Science Education, 2020)
This study results development aims to develop a sepaktakraw smash training model based on smash training aids. This research is based on a needs analysis with a survey method later according to the references and characteristics by looking at the analysis results of smash skill needs analysis model development based on media tools in the Pontianak city athletes packaged in print media products,  namely a training model book. This research uses a development research method that refers to the of Borg and Gall development stages, using Pontianak athletes sample, amounting to 40 people aged 12-17 years and included in the adolescents category. Based on needs analysis data obtained 100% of athletes need the development of a sepak takraw smash training model in Pontianak city athletes based on training aids and analysis by experts developing a sepaktakraw smash training model based on training aids in Pontianak city athletes is feasible so that it can be used in the first stage of group testing limited (stage 3 trials) totaling 20 athletes and field trials in stage 4 totaling 40 concluded that the exercise model was valid so that athletes and trainers could use it during training. Whereas the effectiveness test obtained t-count ? t-table (2.21-2.028 from the calculation results shows that there is a difference between the groups treated with the smash training model material that has been validated by experts (experimental group) experiencing progress results better training compared with a group that implement this type of training of trainers (control group) conclusion from these results is a model of skill training smash sepaktakraw-based tools drills smash in adolescent athletes Pontianak decent used as a medium for training in adolescent athletes.